2009
DOI: 10.1007/s00382-009-0656-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of horizontal resolution on simulation of very extreme US precipitation events in a global atmosphere model

Abstract: We investigate the ability of a global atmospheric general circulation model (AGCM) to reproduce observed 20 year return values of the annual maximum daily precipitation totals over the continental United States as a function of horizontal resolution. We find that at the high resolutions enabled by contemporary supercomputers, the AGCM can produce values of comparable magnitude to high quality observations. However, at the resolutions typical of the coupled general circulation models used in the Fourth Assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
132
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 169 publications
(144 citation statements)
references
References 17 publications
8
132
4
Order By: Relevance
“…Wehner et al, 2010;Kopparla et al, 2013;Prein et al, 2013;Tripathi and Dominguez, 2013). However, several of these studies compare the results on the native grid of each model with observations at resolutions that are often higher than in any of the model configurations.…”
Section: Discussionmentioning
confidence: 99%
“…Wehner et al, 2010;Kopparla et al, 2013;Prein et al, 2013;Tripathi and Dominguez, 2013). However, several of these studies compare the results on the native grid of each model with observations at resolutions that are often higher than in any of the model configurations.…”
Section: Discussionmentioning
confidence: 99%
“…The output from the highest resolution version of a global atmospheric model used in the earlier study by Wehner et al (2010), the Community Atmospheric Model (fvCAM2.2) is also analyzed in some figures below. This data spans a slightly different period, 1979-1996, but provides a useful comparison in this study to a high-resolution global model.…”
Section: The Narccap Regional Models and Observationsmentioning
confidence: 99%
“…This return period length is chosen both to be comparable to previous studies (i.e. Kharin et al 2007;Wehner et al 2010) and also to mitigate uncertainty in the fit of the extreme value distributions. This latter point is discussed in some detail in Sect.…”
Section: Introductionmentioning
confidence: 99%
“…However, to date, studies have only demonstrated the effects of high-resolution on rainfall through single climate model, but not various models. Kopparla et al 2013;Schiemann et al 2014;Volosciuk et al 2015;Wehner et al 2010;Yang et al 2014). Furthermore, these studies have mainly considered extreme rainfall over a global or continental (e.g., the USA) scale, but few have focused on the Asian monsoon region.…”
Section: Introductionmentioning
confidence: 99%